Estudo histopatológico das lesões viscerais da Erliquiose Monocítica Canina na fase crônica - Sanches, Carolina Dias de Campos [UNESP] (2015)
Canine Monocytic Ehrlichiosis (CME) is an infectious disease, potentially fatal, caused by Ehrlichia canis, transmitted by Rhipicephalus sanguineus. The course of the disease is divided into three stages: acute, chronic and subclinical. The aim of this study was to evaluate the pathological lesions that occurred in the parenchyma and the vascular endothelium of the brain, heart, lung, liver, kidney, spleen and mesenteric lymph node of 16 dogs that died affected by CME in the chronic phase. These animals showed neurological signs, but in microscopic evaluation showed no injury to justify these symptoms. In the heart it was possible to notice the presence of visible vascular abnormalities, such as disseminated intravascular coagulation, necrosis of the myocytes near these vessels, congestion and bleeding due to severe thrombocytopenia developed during infection. In the lung was noted pneumonia in most animals studied. The liver also appeared affected, but not directly by infection, but as a result of other harmful factors related to the disease. In all evaluated kidneys showed this glomerulonephritis. In all 16 animals can be noted splenomegaly. The mesenteric lymph node is not a very studied structure in animal CME, but you may notice a large plasma cell infiltrate. However, the vasculitis was responsible for much of the lesions, predominant being the plasma cell infiltrate